(NsO^INENIQ(B: [1885-1886] /s (N~ASTX (B4s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1976)
(NwO (B4 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI RASSKAZY I @MORESKI NAPISANNYE (B1885-1886 (NGG(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (N`MORESKIs